Pengetahuan, sikap dan kepatuhan mengkonsumsi tablet zat besi selama kehamilan - Naili Rahmawati; Siti Hajah Nurhajijah (Holistik Jurnal Kesehatan, 2021)
Knowledge, attitude, and practice of pregnant women in Bandung about intake of iron supplementsBackground: Iron deficiency anemia is a decrease in the number of red blood cells caused by too little iron. According WHO (World Health Organization), in developing countries there are 40% of maternal deaths related to anemia during pregnancy. The frequency of pregnant women in Indonesia who experience anemia is still very high, namely 63.5% compared to only 6% in America. The number of pregnant women who experience anemia is due to a lack of knowledge of the mother, amounting to 45.6% of pregnant women do not know the consequences of anemia, do not regularly consume Fe tablets, and do not understand how to consume Fe tablets properly. Purpose: To determine the Knowledge, attitude, and practice of pregnant women in Bandung about intake of iron supplementsMethod:  Quantitative research with a cross-sectional approach. Data collected using primary data, conducted in August - September 2019. The population was pregnant women at private clinics. Sampling was carried out using the accidental sampling technique of 30 people. Data got by interviewing the questionnaire instrument. Analysis of the data used using the Spearman test.Results: Finding of the variable age at risk (≥35 years) of 22 (73.33%) respondents, higher education 21 (70%) respondents, as housewives 15 (50%) respondents, multigravida parity 18 (60%) ) respondents. Poor of knowledge 16 (53.33%) respondents, positive attitude 18 (60%) respondents, compliance intake of iron supplements  18 (60%) respondents.Conclusion: There is a significant relationship of knowledge, attitude, and compliance intake of iron supplements (p-value <0.05).Keywords: Knowledge; Attitude; Pregnant women; Compliance; Intake of iron supplementsPendahuluan: Anemia defisiensi zat besi adalah perurunan jumlah sel darah merah yang disebabkan oleh zat besi yang terlalu sedikit. Menurut WHO (World Health Organization), di negara berkembang terdapat 40 % kematian ibu berkaitan dengan anemia dalam kehamilan. Frekuensi ibu hamil di Indonesia yang mengalami anemia masih sangat tinggi yaitu 63,5% dibandingkan di Amerika hanya 6 %. Banyaknya ibu hamil yang mengalami anemia disebabkan karena kurangnya pengetahuan ibu, sebesar 45,6% ibu hamil tidak mengetahui akibat dari anemia, tidak teratur dalam mengkonsumsi tablet Fe, dan tidak memahami cara mengkonsumsi tablet Fe secara tepat.Tujuan: Mengetahui adanya hubungan pengetahuan, sikap dan kepatuhan mengkonsumsi tablet zat besi selama kehamilanMetode: Penelitian kuantitatif dengan pendekatan cross sectional. Data yang dikumpulkan menggunakan data primer. Penelitian dilakukan pada bulan Agustus - September 2019. Populasinya ibu hamil di Praktik Mandiri Pengambilan sampel dilakukan dengan teknik accidental sumpling sebanyak 30 orang. Data yang diperoleh dengan wawancara instrument kuesioner. Analisis data yang digunakan menggunakan uji Spearman.Hasil: Didapatkan variabel usia beresiko (≥35 tahun) 22 (73,33%) responden, pendidikan tinggi 21 (70%) responden, pekerjaan ibu rumah tangga 15(50%) responden, paritas multigravida 18(60%) responden pengetahuan buruk sebanyak 16 (53.33%) responden, sikap positif 18 (60%) responden, dan kategori patuh sebanyak 18 (60%) responden.Simpulan: Adanya hubungan antara pengetahuan, sikap dan kepatuhan mengkonsumsi tablet zat besi selama kehamilan (p-value < 0,05).